Uji Aktivitas Antibakteri dan Antibiofilm Fraksi Biji Kelengkeng (Euphoria longan Lour. Steud.) terhadap Staphylococcus aureus ATCC 6538 - Prasety, Oda Shantina; Soegianto, Lisa; Wijaya, Sumi (Jurnal Farmasi Sains dan Terapan, 2019)
Longan (Euphoria longan Lour. Steud.) has an antibacterial potential. Longan seed is one part of Longan that has antibacterial activity. This study was conducted to determine the antibacterial and antibiofilm activity of longan seed fraction (Euphoria longan Lour. Steud.) against Staphylococcus aureus ATCC 6538. In this study, the extract was obtained from maceration using 96% ethanol and it was fractionated by liquid-liquid solvent method using nhexane, ethyl acetate, and water. Each fraction prepared at concentration 100000 ppm, and then the antibacterial activity on Staphylococcus aureus was determined by well diffusion method, antibiofilm activity using microdilution method, and phytochemical screening to determine the metabolite compounds that have antibacterial and antibiofilm activity using thin layer chromatography. The results showed that the diameter of growth inhibition in ethyl acetate fraction with a concentration of 100000 ppm was 14.59 mm ± 0.01, n-hexane fraction at 7.15 mm ± 0.63 and water fraction of 12.52 mm ± 0.40. Antibiofilm test results showed that the percentage of growth inhibition of biofilm on the fraction of ethyl acetate with a concentration of 100000 ppm was 99.08%. Phytochemical screening using thin layer chromatography carried out on the fraction of ethyl acetate and showed that the fraction contains tannin/polyphenols, triterpenoid saponins and flavonoids.